PENGARUH BIAYA PENDIDIKAN DAN DISIPLIN BELAJAR TERHADAP PRESTASI BELAJAR SISWA MTS AL-HUSNA PONTIANAK UTARA - Shofiyah Hasanah; Herkulana Herkulana; Husni Syahrudin (Universitas Tanjungpura, 2022)
This study aims to examine and analyze the effect of education costs and learning discipline on the learning achievement of MTS Al-Husna North Pontianak students. This form of research is quantitative research with a survey type of research. The sample in this study was 75 students of classes VII, VIII and IX at MTS Al-Husna North Pontianak. The sampling method is Simple Random Sampling. Data were collected with questionnaires that had been tested for reliability validity. The data analysis technique used is the SPSS prgram.22. The results of this study showed that after conducting a linear regression test on the variable X1 on Y, it was said to have an influence with the regression equation Y = 82.200 + 0.717X1 with an influence of 80.7%. In the variable X2 against Y, it is said to have an influence with the regression equation Y=86.067+0.625X2 with an influence of 62.1%. In the variables X1 and X2 against Y it is said to have an influence with the regression equation Y= 84.263 + 0.391 X1+0.382X2 with an influence of 90.1%. Then the signification value of 0.000 is smaller than 0.05 so that it can be concluded that H0 is rejected and Ha is accepted which means that there is an influence between